EVALUASI KANDUNGAN Salmonella sp. DAGING BROILER DI PASAR-PASAR TRADISIONAL KABUPATEN TANGGAMUS - Etika, Tiara Nur; Santosa, Purnama Edy; Suharyati, Sri (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
This research aims to know the content of Salmonella sp. in broiler meat in traditional markets Tanggamus Regency. Analysis of Salmonella sp. in broiler meat was conducted in December 2016 – January 2017 in the laboratory of veterinary public health, Regional Veterinary Hall III Bandar Lampung. This research used 28 samples that collected by random sampling in the morning and daylight of all traditional markets in the Tanggamus Regency like Talang Padang, Gisting, Kota Agung and Wonosobo. The obtained data were made in tabulation form and analyzed descriptively to the sample condition that collected in the morning and daylight. The results of this research show that the content of broiler meat of Salmonella sp. was negative. Content of broiler meat of Salmonella sp. from traditional markets Tanggamus Regency in accordance with National Standard of Indonesia SNI 7388:2009. Key Words: Broiler, Salmonella sp., Traditional Market, Tanggamus